Medical Organizations on the Insurance Market in Russia - Kozminykh, Olga V. (International Journal of Psychosocial Rehabilitation, 2020)
Purpose – In order to confirm or disprove the hypothesis that medical organizations play the role of intermediaries on the market of insurance products we conducted a study about the nature of intermediation carried out on the market of insurance products, as well as the analysis of the activities of medical organizations and their impact on the development of the insurance market. Design/Methodology/Approach – Using a systematic approach, structural-functional method, comparative and system analysis, visualization and generalization of the obtained results, we determined that medical organizations are the intermediaries on the market of insurance products. Medical organizations were not considered to be participants on the insurance products market. To fill this gap, it was hypothesized. Findings – Perspectives were developed to improve the reliability of medical organizations as intermediaries on the medical insurance market; recommendations given; fraudulent actions of medical organizations observed; situation in Russian Federation is compared with number of other countries. Practical Implications – The found development perspectives will reduce the risk of opportunistic behavior of medical organizations, which is often realized in voluntary health insurance. The reduction of tort risks for insurers that provide medical insurance will reduce the number of fraudulent payments, which will have a positive impact on the tariff policies of insurance companies and increase the reliability of the medical insurance market Originality/Value – The aspects of intermediation of medical organizations are analyzed from the point of view of insurance theory.